A transferrable and integrative type I-F Cascade for heterologous genome editing and transcription modulation. Issue 16 (22nd June 2021) - Xu, Zeling; Li, Yanran; Cao, Huiluo; Si, Meiru; Zhang, Guangming; Woo, Patrick C Y; Yan, Aixin
Abstract: The Class 1 type I CRISPR–Cas systems represent the most abundant and diverse CRISPR systems in nature. However, their applications for generic genome editing have been hindered due to difficulties of introducing the class-specific, multi-component effectors (Cascade) in heterologous hosts for functioning. Here we established a transferrable Cascade system that enables stable integration and expression of a highly active type I-F Cascade in heterologous bacterial hosts for various genetic exploitations. Using the genetically recalcitrant Pseudomonas species as a paradigm, we show that the transferred Cascade displayed substantially higher DNA interference activity and greater editing capacity than both the integrative and plasmid-borne Cas9 systems, and enabled deletion of large fragments such as the 21-kb integrated cassette with efficiency and simplicity. An advanced I-F-λred system was further developed to enable editing in genotypes with poor homologous recombination capacity, clinical isolates lacking sequence information, and cells containing anti-CRISPR elements Acrs. Lastly, an 'all-in-one' I-F Cascade-mediated CRISPRi platform was developed for transcription modulation by simultaneous introduction of the Cascade and the programmed mini-CRISPR array in one-step. This study provides a framework for expanding the diverse type I Cascades for widespread, heterologous genome editing and establishment of editing techniques in 'non-model' bacterial species.